Ethanol dehydrogenation over copper supported on carbon macrofibers; Mendeleev Communications; Vol. 27, iss. 2 - Ponomareva E. A. Ekaterina; Krasnikova I. V. Irina; Egorova E. V. Ekaterina; Mishakov I. V. Iljya Vladimirovich; Vedyagin A. A. Aleksey Anatolievich (2017, 2017)
Title screen